Non-volatile resistive switching in the dielectric superconductor YBa 2Cu3O7-δ - Acha, Carlos Enrique (2009)
We report on the reversible, non-volatile and polarity-dependent resistive switching between superconductor and insulator states at the interfaces of an Au/YBa2Cu3O7-δ (YBCO)/Au system. We show that, upon application of electric pulses, the superconducting state of YBCO in regions near the electrodes can be reversibly removed and restored. In addition, four-wire measurements reveal that pulsing also induces significant non-volatile changes in the bulk resistance. We argue that our observations are compatible with a scenario where the switching effect is due to migration of oxygen ions along grain boundaries that control the inter-grain superconducting coupling. © 2009 IOP Publishing Ltd.